HEXAGON FRAUD PERSPECTIVE ON FINANCIAL STATEMENT FRAUD IN INDONESIA INSURANCE COMPANIES - Mursalam Salim; Aldrin Akbar Mohammad; Sutisna Entis; Mawadda Anwar Aini (KRISNA: Kumpulan Riset Akuntansi, 2024)
Financial statement fraud is something that causes economic losses and results in a loss of investor confidence. Therefore, company management needs to identify what factors influence the company in committing fraud. One approach to detecting fraud is to use the fraud hexagon model. This model consists of stimulus, opportunity, rationalization, capability, ego, and collusion. This research is explanatory research that aims to investigate the possible factors of financial statement fraud using a fraud hexagon perspective. The objects used as research samples are 15 insurance companies registered on the IDX during 2019 - 2022. This research uses the F-Score model to separate companies that have experienced fraud and uses logistic regression as data analysis. The results of his study show that the elements of opportunity, rationalization, and ego influence financial statement fraud. Meanwhile, the elements of stimulus, capability, and collusion do not affect financial statement fraud.